Chinese Modernization and the Prospects of World Modernization: A Review of the 16th Forum of the World Association for Political Economy - Zhihong Luo; Xiaoqin Ding (World Review of Political Economy)
The 16th forum of the World Association for Political Economy took place in Pingtan, Fujian province, China, on September 25–27, 2023. The theme was “Chinese Modernization and the Prospects of World Modernization.” Experts and scholars from over 20 countries and regions focused on the theme, discussing methods of political economy and theories of modernization research, Chinese modernization and global political and economic structures, the practice of Chinese modernization and the innovation and development of mesoeconomics, research on the political economy of socialism with Chinese characteristics, comparisons of Chinese modernization and capitalist modernization, ecological civilization and the practical path of Chinese modernization, the basic principles of Marxist economics, and the special characteristics of Chinese modernization. The forum has deepened the knowledge and understanding of scholars about Chinese modernization and global modernization, while also contributing wisdom to support people all over the world in pursuing an independent modernization path and promoting the modernization process.